Stability Augmentation of a Fixed Speed Wind Generator by Using VSWT-PMSG - Tasneem, Zinat; Sheikh, M.R.I.; Pinky, A. N. (Journal of Technology Innovations in Renewable Energy, 2014)
This paper proposes an optimized model of a variable speed wind turbine equipped with permanent magnet synchronous generator (VSWT-PMSG) which also has been used for the stability augmentation of a wind farm including fixed speed wind generators, like Induction generator (IG). An effective control strategy with two-level IGBT converter-inverter set along with DC link capacitor and maximum power point tracking (MPPT) system assures the real power exchange to the grid and also a perfect reactive power compensation that maintains the grid side voltage constant. Moreover, it is shown that the proposed model can enhance the stability of a conventional IG based wind farm when used in combination with PMSG. Thus it eliminates the need of external controlling devices and makes the system simple and cost effective. A comparison for the stability augmentation capability between IG and PMSG has been explained. Both the dynamic and transient analyses of the proposed system have been carried out by using the laboratory standard power system software package, PSCAD/EMTDC.